2013
DOI: 10.2147/ppa.s44698
|View full text |Cite
|
Sign up to set email alerts
|

Medication adherence in patients with type 2 diabetes mellitus treated at primary health clinics in Malaysia

Abstract: PurposeDiabetes mellitus is a growing global health problem that affects patients of all ages. Even though diabetes mellitus is recognized as a major chronic illness, adherence to antidiabetic medicines has often been found to be unsatisfactory. This study was conducted to assess adherence to medications and to identify factors that are associated with nonadherence in type 2 diabetes mellitus (T2DM) patients at Primary Health Clinics of the Ministry of Health in Malaysia.Materials and methodsThe cross-sectiona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

20
59
5
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(103 citation statements)
references
References 21 publications
20
59
5
3
Order By: Relevance
“…In our study, females were more likely to be adherent to their therapies than males, which is consistent with the previously reported study by Elsous, et al in Gaza (16). Contrary to other studies, the older patients in our study were poorer adherent to treatment than younger patients, but it was not statistically significant (19,21,22). In this case, our result is consistent with the study by Donnan et al (13).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In our study, females were more likely to be adherent to their therapies than males, which is consistent with the previously reported study by Elsous, et al in Gaza (16). Contrary to other studies, the older patients in our study were poorer adherent to treatment than younger patients, but it was not statistically significant (19,21,22). In this case, our result is consistent with the study by Donnan et al (13).…”
Section: Discussionsupporting
confidence: 92%
“…However, Sontakke et al re-ported results similar to ours, and the high, moderate, and low adherence to treatments for type 2 diabetes among their participants was 0%, 26%, and 74%, respectively (10). The widely varying rates of medication adherence could be attributed to factors related to the study settings, socio-economic status, and metrics used for adherence assessment (14,16,19). Diabetic patients in our study reported several factors that hindered adherence to nonmedication recommendations for control of their disease.…”
Section: Discussionsupporting
confidence: 71%
“…However, adherence to anti-diabetes medication was better of all self-care practices [17]. This could be due to either over reliance on medication or its free availability, or the ease to practice it compared to the other components which require more commitment [18].…”
Section: Discussionmentioning
confidence: 99%
“…Penelitian yang dilakukan sebelumnya oleh menunjukkan bahwa semua perilaku perawatan diri yang tepat secara positif berkaitan dengan kontrol glikemik yang baik pada pasien diabetes (Luo & liu, 2015;Gao, et al, 2013). Akan tetapi pada penelitian Ahmad, Ramli, Islahudin, dan Paraidathathu (2013) dan Nunez-smith (2011) menyatakan bahwa tidak semua kegiatan dalam self-care terhadap pengelolaan diabetes memengaruhi kontrol glikemik yang baik pada pasien dengan diabetes (Ahmad, Ramli, Islahudin, & Paraidathathu, 2013;Nunez-smith, 2011).…”
Section: Pendahuluanunclassified